Znaki na dnach naczyń z dworu obronnego w Orłowie - Barnycz-Gupieniec, Romana (Acta Universitatis Lodziensis. Folia Archaeologica, 1989)
Archeological investigations of the fortified manor in Orłów, parish of Bedlno, province of Płock provided a very interesting pottery material. In total, 12 318 fragments of utensils included 1390 bottoms of which 22 with signs were gathered. The choice of signs of Orłów utensils is rather inconspicuous. The sign of a simple cross drawn with a thin line of arms length from 2 to 3 cm appearing on 17 specimens was the most common. In four cases the sign of Maltese cross and in one case the cross inscribed in a circle were observed. It is hard to determine whether there are identical signs among them because of the bad state of preserved specimens (the majority of them is rubbed away). Almost all bottoms with signs belong to group A – i.e. pottery so called "traditional" and only three should be prescribed to group AB – possessing features of both traditional and "progressing" technology (biscuit-fire in reduction process). All signed bottoms date back to the second half of the XIIIth century – the first half of the XVth century. Analysing the function of signs three fundamental conceptions arise: proprietary signs of producers, proprietary signs of buyers and magic signs. As to Orłów signs the last conception seems to be the most probable.